18th International Parallel and Distributed Processing Symposium, 2004. Proceedings.
DOI: 10.1109/ipdps.2004.1303192
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of NIC resource usage for offloading MPI

Abstract: Modern cluster interconnection networks rely on pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 24 publications
(29 reference statements)
0
32
0
Order By: Relevance
“…Even at small scale, applications can spend a large portion of their time waiting for messages to arrive and reductions in bandwidth or failure to substantially improve latency over conventional methods can greatly exacerbate this problem. A custom NIC that integrates the network controller, and in some cases the messaging protocol, onto the chip to reduce power, is expected to also increase messaging throughput and communication performance [2,17]. Although there is a risk of choosing a network interface that is not compatible with all the underlying data communication layers, applications that send small and frequent messages are likely to benefit from such integration.…”
Section: Integrated Componentsmentioning
confidence: 99%
“…Even at small scale, applications can spend a large portion of their time waiting for messages to arrive and reductions in bandwidth or failure to substantially improve latency over conventional methods can greatly exacerbate this problem. A custom NIC that integrates the network controller, and in some cases the messaging protocol, onto the chip to reduce power, is expected to also increase messaging throughput and communication performance [2,17]. Although there is a risk of choosing a network interface that is not compatible with all the underlying data communication layers, applications that send small and frequent messages are likely to benefit from such integration.…”
Section: Integrated Componentsmentioning
confidence: 99%
“…On the other hand, a lot of messages comparable to the number of nodes stay in the unexpected message queue in some case. For example, FT and IS of NAS Parallel Benchmarks (NPB) is so according to the research by Brightwell [4]. He reported that in FT the average search length for the unexpected message queue at 128 nodes is 20% or more than the number of nodes, and that it increases in proportion to the number of nodes.…”
Section: Unexpected Message Searching Latencymentioning
confidence: 99%
“…In Brightwell's work [4], a significant portion of the messages received by the NAS Parallel Benchmarks (NPB)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work, we collected and analyzed data related to the MPI posted receive and unexpected message queues, and measured expected versus unexpected messages [26]. We used these measurements to characterize the amount of processing and memory resources that are needed for offloading MPI semantics.…”
Section: A Mpi Profilingmentioning
confidence: 99%